2012
DOI: 10.1590/s1516-35982012001000020
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of benchmarks of milk production systems in Minas Gerais

Abstract: The objective of this study was to identify and quantify benchmarks of milk production systems. The technological profile and size, livestock and economic indicators of sixteen farms in the region of Triângulo Mineiro were analyzed. Indicators correlated with rate of return on capital (RRC) were identified and quantified in four scenarios of RRC (6, 8, 10 and 12% per year). The correlated indicators and their respective values in the four scenarios were: land (99, 90, 81 and 73 ha); relation of total cows in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 3 publications
(10 reference statements)
5
13
0
1
Order By: Relevance
“…The average productivity per lactating cow was consistent with the production system used, which was characterized by crossbred animals (1/2 to 7/8, Dutch x Zebu) and mid-level management (GLÓRIA et al, 2006), and was higher than the average productivity of samples evaluated in other regions (FASSIO et al, 2006;OLIVEIRA, et al, 2007;CAMILO NETO et al, 2012). However, this production would be higher, since 7/8 animals, for example, would respond more efficiently if a better environment was provided to them.…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…The average productivity per lactating cow was consistent with the production system used, which was characterized by crossbred animals (1/2 to 7/8, Dutch x Zebu) and mid-level management (GLÓRIA et al, 2006), and was higher than the average productivity of samples evaluated in other regions (FASSIO et al, 2006;OLIVEIRA, et al, 2007;CAMILO NETO et al, 2012). However, this production would be higher, since 7/8 animals, for example, would respond more efficiently if a better environment was provided to them.…”
Section: Resultssupporting
confidence: 61%
“…Camilo Neto et al (2012), considering the SEBRAE Educampo Project, reported that the income from the milk was 70.1 to 80% of the income of the activity in balanced production systems, producing 8.1 to 12 liters per lactating cow per day (range in which the evaluated samples of the present study are found), results that are within the recommended rates. The expenses with concentrate feed in relation to the milk gross income is an important indicator of economic efficiency.…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations